A Recessively Inherited Risk Locus on Chromosome 13q22-31 Conferring Susceptibility to Schizophrenia. (7th November 2020) - Mahmood, Tariq; El-Asrag, Mohammed E; Poulter, James A; Cardno, Alastair G; Tomlinson, Anneka; Ahmed, Sophia; Al-Amri, Ahmed; Nazari, Jamshid; Neill, Joanna; Chamali, Rifka S; Kiwan, Nancy; Ghuloum, Suhaila; et al.
Abstract: We report a consanguineous family in which schizophrenia segregates in a manner consistent with recessive inheritance of a rare, partial-penetrance susceptibility allele. From 4 marriages between 2 sets of siblings who are half first cousins, 6 offspring have diagnoses of psychotic disorder. Homozygosity mapping revealed a 6.1-Mb homozygous region on chromosome 13q22.2-31.1 shared by all affected individuals, containing 13 protein-coding genes. Microsatellite analysis confirmed homozygosity for the affected haplotype in 12 further apparently unaffected members of the family. Psychiatric reports suggested an endophenotype of milder psychiatric illness in 4 of these individuals. Exome and genome sequencing revealed no potentially pathogenic coding or structural variants within the risk haplotype. Filtering for noncoding variants with a minor allele frequency of <0.05 identified 17 variants predicted to have significant effects, the 2 most significant being within or adjacent to the SCEL gene. RNA sequencing of blood from an affected homozygote showed the upregulation of transcription from NDFIP2 and SCEL . NDFIP2 is highly expressed in brain, unlike SCEL, and is involved in determining T helper (Th) cell type 1 and Th2 phenotypes, which have previously been implicated with schizophrenia.